Strong democracy, weak state: The political economy of Ghana’s stalled structural transformation - Resnick, Danielle (International Food Policy Research Institute, 2019)
This chapter has shown that Ghana’s reputation for upholding political rights and civil liberties since the country’s democratic transition in 1992 is well deserved. As Africa’s only institutionalized two-party system, competitive elections have enforced a commitment to the poor and a broad swathe of voters, evidenced by an impressive national health insurance scheme and an extensive social transfer program. Resources also have been heavily invested in health and education, resulting in substantial improvements in social outcomes. Foreign direct investment is attracted by the country’s political stability and openness. Compared to the country’s years of political instability prior to the 1980s, when ideological differences resulted in high levels of policy volatility, substantive partisan differences between the NDC and NPP have narrowed on key issues. As Throup et al. (2014: 155) note with respect to agriculture, there is now a bi-partisan consensus on key policies: “the peasantry must be encouraged, nontraditional crops must be promoted, development must be brought to the North [through the Savannah Accelerated Development Authority], and investment on infrastructure should be prioritized.”